Ion exchange membranes for regeneration of hydrochloric acid from etching solutions - Bolshanina, Svitlana; Serdiuk, Vasyl; Ponomarova, Ludmyla; Yanovska, Anna; Ableev, Alexey (My University, 2018)
The process of regeneration of utilized hydrochloric acid etching solutions using electrochemical equipment with ion exchange membranes was examined. The products of cathode reactions were studied. It was proved that the waste solution was not only purified from contaminate ions, but the acid content increased during the electrolyzer operation.Розглядається процес регенерації відпрацьованих травильних розчинів на основі хлоридної кислоти з використанням електрохімічних пристроїв з іонообмінними мембранами. Вивчено продукти реакцій на катоді. Доведено, що при роботі електролізера відпрацьований травильний розчин не тільки очищується від забруднюючих його іонів, але і збільшується вміст кислоти.
Keywords: membrane; ion exchange membrane; electrodialysis; chloride acid; regeneration; мембрани; іонообмінні мембрани; електродіаліз; хлоридна кислота; регенерація